Clinical pharmacy services in mental health in Europe: a commentary paper of the European Society of Clinical Pharmacy Special Interest Group on Mental Health - Stuhec, Matej; Hahn, M; Taskova, I; Bayraktar, I; Fitzgerald, I; Molitschnig, L; Tatarević, A; Lindner, N; Agnoletto, L; da Costa, F Alves (International journal of clinical pharmacy, 2023)
A large proportion of the world's disease burden is attributable to mental illnesses. Although effective interventions are available, many patients still have limited access to evidence-based treatments. Aside from access, treatment gaps, including inappropriate medication selection and monitoring, are also routinely recognised. Mental health clinical pharmacists can help address these gaps and enable patients to receive optimised pharmaceutical care, particularly appropriate medication selection and monitoring. The European Society of Clinical Pharmacy (ESCP) Special Interest Group on Mental Health was established to improve standardised service provision in mental health settings across Europe. The Special Interest Group identified significant barriers (predominantly associated with reimbursement and position within the multidisciplinary team) to effective pharmaceutical care amongst those with mental illnesses. This commentary presents recommendations to address these gaps through improved mental health clinical pharmacy service provision.
Keywords: farmacie; farmaceuti; Pharmacy; Pharmacy Service, Hospital; Public Opinion; duševní zdraví; lidé; Europe; nemocniční lékárny; Evropa; Mental Health; Pharmacists; veřejné mínění; Humans